Childhood adversity and inflammatory processes in youth: a prospective study - Natalie Slopen (European Journal of Psychotraumatology, 2012)
Rationale/statement of the problem : Retrospective studies show that childhood adversity is associated with systemic inflammation in adulthood. Few prospective studies have examined whether childhood adversity influences inflammation in an observable manner during childhood or adolescence and whether these effects are sustained over time. Methods : Using longitudinal data from the Avon Longitudinal Study of Parents and Children, we examined associations between acute adverse events at seven time points prior to age 8 and inflammation at ages 10 and 15. Inflammatory markers at age 10 included interleukin-6 (IL-6; N=4,655) and C-reactive protein (CRP; N=4,647), and CRP was measured again at age 15 (N=3,286). We further evaluated whether body mass index (BMI), depression, or cigarette smoking mediated associations between adverse events and inflammation. Results : Adverse events in middle childhood (occurring between ages 6 and 8), as well as cumulative adversity between the ages of 1.5 and 8 years, were associated with higher levels of IL-6 and CRP at age 10. Adverse events occurring in early childhood (age 1.5) or middle childhood (age 8), and cumulative adversity between the ages of 1.5 through 8 years predicted increased levels of CRP at age 15, and these associations persisted after adjustment for CRP at age 10. Some, but not all, of these associations were mediated by BMI. Conclusions : This study documents that exposure to adverse events prior to age 8 is associated with elevated inflammation at age 10 and in mid-adolescence. These findings provide prospective evidence for a biological mechanism by which early experiences may shape long-term health.